Molecular Characterization of Group A Human Rotavirus among Hospitalized Children and Adults in Bangladesh: Finding of Emerging G12 Strain - Paul, SK; Ahmed, MU; Hossain, MA; Mahmud, MC; Bhuiyan, MR; Saha, SK; Tabassum, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):16-26. The abstract of this article is available on the PubMed website